Testicular granulosa cell tumor, adult type - Gupta Anshu; Mathur S; Reddy Chada; Arora B (Wolters Kluwer Medknow Publications, 2008)
Granulosa cell tumor (GCT) of the adult type is a rare and slow-growing neoplasm in the testis. This tumor may be associated with endocrine manifestations and resemble classic GCT of the ovary morphologically. It has a potential for distant metastasis or recurrence late in the clinical course. We report a case of granulose cell tumor of the testis, adult type.